Non-febrile generalized pustular psoriasis of childhood followed by plaque psoriasis of the face. - Garofalo, L. (European Journal of Pediatric Dermatology, 2023)
Psoriasis has a highly variable clinical spectrum ranging from mild, scarcely symptomatic and inconspicuous forms to severe forms, either due to the general involvement as in generalized pustular psoriasis or to the affected site, for example the face. The case of a 10-year-old boy with non-febrile generalized pustular psoriasis who after 11 years presented persistent plaque psoriasis of the face was described.